Impact of plastic pesticide containers on agricultural soils: a cultural problem of Ecuadorian agriculture - Tigrero Zapata, Gabriela Jamilex; Sánchez Iznaga, Ángel Lázaro; Verdesoto Arguello, Alexis Eduardo; Saucedo Aguiar, Álvaro Edmundo; Camacho Bustamante, Luis Carlos; Soto Montoya, Carmen Luisa (Ingeniería Química y Desarrollo, 2024)
Microplastics are generated by the degradation of larger fragments in the environment, thanks to ultraviolet light that can fragilize the materials, allowing them to be a source of severe toxins that affect the microbiota existing in the soil. The impact produced by plastics from pesticide containers in agriculture carried out by small and medium farmers on the soil is one of the cultural problems studied in this work. Through the implementation of surveys to forty farm owners and associates in legally established organizations in the rural area of the Puebloviejo and Quinsaloma canton, with open and closed questions, managed in a descriptive and informative way and analyzed quantitatively, data were obtained such as schooling, productivity, training and management of agricultural waste such as those common plastics used in their daily agricultural routine among them pesticide containers, PVC irrigation pipes, drip irrigation tapes and drip irrigation tapes, among others, drip irrigation tapes or covers for transplanting in their different labors allow increasing the sources of plastic materials, obtaining unflattering data on the handling and management of pesticide containers, and other common plastics, understanding the impact of contamination by pesticide plastics used by farmers, reflected in 93%, concluding that farmers do not return the containers and/or do not comply with their legal obligations, mainly due to lack of public support for control, motivation, lack of knowledge and awareness.